COASTAL RESOURCE MANAGEMENT BY RURAL WOMEN FOR BLUE ECONOMY IN PENGUJAN, BINTAN REGENCY - Rizki, Muhammad; Syahputro, Satrio Bimo; Indriaty, Novica; Beby, Daeylen; Asti, Dewi (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2026)
The implementation of the Blue Economy concept is highly significant for archipelagic nations such as Indonesia. However, the role of women in coastal and marine resource management often lacks adequate attention and recognition, including in Pengujan Village, Bintan Regency. This research aims to deeply examine the role of women in Pengujan Village in managing coastal resources toward realizing the Blue Economy. The study adopts a qualitative methodology. Data collection techniques include semi-structured interviews, non-participant observation, and documentation. A purposive sampling technique was used to select eight informants. The findings reveal that the coastal resources involving women in their management are marine animals, beaches, and marine plants. The women's roles in resource management encompass sourcing, processing, marketing, and maintenance. Several factors support their role in coastal management, including the government, family, private sector, and peers. Conversely, constraining factors include weather conditions, economic constraints, security issues, management skills, resource scarcities, family constraints, and equipment limitations. Based on these findings, it is recommended that the Pengujan Village government enhance women's understanding of the Blue Economy and coordinate with the regional government to improve the management and marketing skills of women in Pengujan Village.